Struktur Nafkah Rumah Tangga Masyarakat Suku Mee Di Kelurahan Girimulyo Nabire Papua Tengah - Dharsono, Wardhana Wahyu; Liborang, Hans Frits; Waromi, Ali; Bogar, Deby Siska (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
The purpose of this study was to determine the Household Income Structure of the Mee tribe community in Girimulyo Village, Nabire District, Nabire Regency. This research was conducted using quantitative descriptive method. The data used in this study are primary data and secondary data. The informants used in this study were 28 people who were Mee Tribe People in Girimulyo Village. The purpose of the research on the Mee Tribe Community Household Income Structure in Girimulyo Village, Nabire District, Nabire Regency, obtained the Mee tribe community income structure seen from gender, differences in the Mee tribe men's income structure with women whether influenced by human capital (human capital), Mee tribe women's activities in relation to finding sources of income.